Analysis of Product-Service Systems in Micro Small and Medium Enterprises (MSMEs) for Sales Sustainability - Kolose Saputra; Nanang Alamsyah (Telaah Bisnis, 2023)
The purpose of this study is to analyze the ability of MSMEs to implement PSS and provide recommendations to MSMEs in terms of strategies for utilizing PSS in MSMEs. This research was conducted on four MSMEs, two in the South Jakarta area and two in the Depok area. The data collection technique used a questionnaire. The type of research method used in this research is descriptive-qualitative analysis. The data analysis method was carried out using the PSS Matrix analysis method by inputting the results of the questionnaire data. The results of this study indicate that MSME A qualifies for the use-oriented category, MSME B qualifies for the product-oriented and use-oriented categories, MSME C qualifies for the product-oriented and use-oriented categories, and MSME D qualifies for the use-oriented and result-oriented categories.